(untitled) (Research, Society and Development, 2020)
This article objective to report and reflect on the teacher experience of the Mental Health Nursing discipline about the use of methodological resources, as the use of the Whatsapp application in schoolroom activities, on purpose of enable the student the use of social networks and the communication virtual in learning process, as well as a formation more reflective for acting in the health system. This is an experience report about the use of the Whatsapp application as a tool for strategy methodological during the discipline of Nursing in Mental Health of the undergraduate Nursing course. Firstly, used the application in a group format to explore information available on the internet about user embracement. In a second moment, the students built a concept of user embracement from the information posted in the discussion group. The possibility become the student as protagonist of the teaching-learning process, stimulates and favors meaningful learning, providing a formation of proactive, critical and reflective professionals about their reality. The experience made it possible the student to be a protagonist in his construction of theoretical knowledge, favored learning, making the student part of the process, and a protagonist in this construction. And to teacher, it made it possible to approach the students, and engage in a reflective critical formation.